Effect of age on the pathogenesis of duck tembusu virus in Cherry Valley ducks - Li, Ning; Lv, Chuanwei; Yue, Ruichao; Shi, Ying; Wei, Liangmeng; Chai, Tongjie; Liu, Sidang (Frontiers in Microbiology, 2015)
The effect of host age on the outcome of Duck Tembusu virus (DTMUV) infection was studied in ducks. Three groups of Cherry Valley ducks at 1, 3 and 7 weeks of age were intramuscularly infected with DTMUV to systematically observe the clinical symptoms, pathological changes, tissue viral loads and immune responses. Severe clinical symptoms and neurological dysfunction were observed in 1-week-old ducks as early as 2 day post infection (dpi) and some died at 5 –7 dpi. Three week old ducks showed similar but milder symptoms and no deaths. However, 7-week-old ducks showed only transient loss of appetite. Gross lesions gradually reduced in severity as ducks matured. One week old ducks showed endocardial haemorrhage, splenomegaly, swelling in the lymph follicles of the ileum, liver and kidney swelling with degeneration, and meningeal hyperemia. Three week old ducks showed only mild pathological lesions. No visible lesions were observed in 7-week-old ducks. However, pathological histology analysis demonstrated all infected ducks displayed viral encephalitis. DTMUV could be detected in the brains of 1-week-old ducks as early as 1 dpi and virus titers of most organs in 1-week-old ducks were significantly higher than that of 3- and 7-week-old ducks at 3 –5 dpi. The patterns of IFN-γ, IL-2, and serum neutralizing antibodies were similar, and there were significant difference between the youngest ducks and the older ducks at early infection stage (P<0.05). More important is that although the antibody titers of all infected ducks were similar from 9 dpi to 17 dpi, reduced clearance of virus was observed in the youngest groups comparing with the other two groups, indicating that immune system maturity was more important than the presence of neutralizing antibody. In summary, this study demonstrates that viral pathogenesis is strongest in 1-week-old ducks and the age-related immune response plays an important role in the pathogenesis of DTMUV in ducks.